PENGARUH PENGGUNAAN SISTEM E-MUSRENBANG TERHADAP EFEKTIVITAS PERENCANAAN PEMBANGUNAN: PENGANGGARAN PARTISIPATIF SEBAGAI VARIABEL PEMODERASI - Rohmatulloh, Lailatun; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2018)
This research is aimed to examine empirically the influence of the use of E-Musrenbang system to the effectiveness of development planning at Local Government Work Units of Surabaya city. This research is also aimed to examine empirically whether participatory budgeting moderates the use of E-Musrenbang to the effectiveness of development planning at Local Government Work Units of Surabaya city.The sample collection technique has been carried out by using purposive sampling method. The data has been obtained by issuing questionnaires to the employees of Local Apparaturs Organization which has authority in Musrenbang process, so 16 district level Local Apparaturs Organizations and Planning and Development Agencies of Surabaya city have been selected as samples. The analysis technique has been carried out by using simple regression analysis to examine the influence of the use of E-Musrenbang system to the effectiveness of development planning. Meanwhile, in order to examine participatory budgeting the moderating variable has been conducted by using Moderate Regression Analysis. The result of the research shows that the use of E-Musrenbang system gives positive influence to the effectiveness of development planning. On the contrary, the participatory budgeting cannot moderate the influence of the use of E-Musrenbang to the effectiveness of development planning.Keywords: E-Musrenbang system, development planning, participatory budgeting.